Innovation and improvement in food fortification: Microencapsulation of vitamin B2 and B3 by a spray-drying method and evaluation of the simulated release profiles - Ioana C. Carlan (2021)
Food fortification helps to maintain, improve or correct nutrients requirements. The current paper explored the possibility of using the spray-drying method to produce microparticles with vitamin content suitable for incorporation in fortified food products. Vitamin B2 and vitamin B3 were microencapsulated with six different biopolymers (chitosan, modified chitosan, gum arabic, maltodextrin, sodium alginate and pectin), aiming with this research to highlight the similarities and differences. For these two categories of microparticles product yield, encapsulation efficiency, size and external morphology were determined. Afterward, in vitro release studies were performed under two different in vitro simulated conditions to evaluate: the time required for the vitamin to be released, the best kinetic models (Zero order, Higuchi, Korsmeyer-Peppas and Weibull) to describe the experimental release profiles and the main release mechanisms involved. Stability of the microparticles over 4 months of storage was also evaluated. The overall results lead to a successful microencapsulation process as for both vitamins the encapsulation efficiency reached values higher than 99% and the product yield ranged from 45% to 55% in the case of vitamin B2 and to 58% for vitamin B3. Through SEM characterization microparticles with regular or irregular spherical shape and with the smooth or rough surface were distinguished. The mean size of the microparticles loaded with vitamin B2 ranged in the interval 0.10 - 0.16 mu m and the ones with vitamin B3 between 0.11 and 0.84 mu m, considering a number distribution. With faster (minutes) or slower (hours) release, both types of microparticles showed a very good fitting especially to Weibull kinetic model and proved good stability over time since a vitamin loss lower than 10% was registered.